Pola Pengasuhan Anak Stunting di Kabupaten Bangkalan - Anggi Sintya Dewi; Sugeng Harianto (Jurnal Community, 2023)
The global prevalence of stunting in the world, including in Indonesia, is still high. Parenting patterns of feeding in the First 1000 Days of Life affect nutritional intake which has a direct impact on the incidence of stunting. Support for good nutritional intake requires the ability of mothers to provide care for children. The highest stunting rate in East Java is in Bangkalan Regency. This study aims to find out how the pattern of parenting children in Bangkalan Regency results in high cases of stunting there. This study uses qualitative methods with an ethnomethodological approach to patterns of action. The data collection technique in this article uses in-depth interview techniques with a number of families whose children are stunted. The research sample was taken by purposive sampling. Data on stunting families was taken from the Family Planning Office for Women's Empowerment and Child Protection in Bangkalan Regency. The results of this study indicate that stunting in children is caused by bad parenting. Bad parenting of children due to lack of knowledge of the mother. Suggestions to educational institutions, health centers, and mothers who have toddlers should synergize with each other to improve the nutritional status of toddlers starting from adding insight or knowledge of the importance of good parenting to reduce the risk of stunting.